Prospective Associations Among Youth Assets and Alcohol, Tobacco, and Other Drug Use in a Hispanic Youth Population. Issue 2 (May 2020) - Moser, Lea; Oman, Roy F.; Lensch, Taylor; Clements-Nolle, Kristen
This study's purpose was to determine whether specific youth assets (conceptualized as influencing health behavior at the individual, family, or community level) were prospectively associated with reduced alcohol, tobacco, and other drug use (ATD) in a sample of Hispanic youth. A longitudinal community-based study was conducted with five waves of data collected annually over 4 years. Participants were Hispanic youth (14.1 years old; 53% female) and their parents ( N = 306 youth/parent pairs). Generalized linear mixed models were used to determine the prospective influence of 17 youth assets on ATD over five waves of data. Results indicated that Hispanic youth with three of seven individual-level assets (e.g., educational aspirations), any of four family-level assets (e.g., family communication), or with one of six community-level assets (e.g., positive peer role models) were significantly less likely to engage in ATD. The results suggest that assets protect Hispanic youth from ATD and that family-level assets may be particularly important.